Desmoplastic Infantile Ganglioglioma (DIG):A Case Repor - บุญเรือง รักไทย; อมรฟ้า จิระพร; ช่วงโชติ ชนพ (Thai Journal of Neurological Surgery, 2025)
This is a 3-year-old child presented with repeated vomiting for 2 weeks and subsequently developed right hemiparesis and unsteady gait. Computed tomography of the brain showed a huge left frontal tumor, 6.8 x 7.2 x 6.6 cm causing brain edema and pressure effect. The patient undenwent surgery, and the mass was completely removed. Pathological examination revealed Desmoplastic infantile ganglioglioma (DIG) (WHO 2016 grade I). The patient made remarkable recovery postoperatively.